Ultrastructure of the germinative epithelium in a goat with a 5/15 Robertsonian translocation - Da Cruz Landim Alvarenga, E. F. [UNESP] (My University, 1995)
The spermatogenesis of two goats bearing a 5/15 Robertsonian translocation was investigated by electron microscopy. There was no dramatic change in the morphology of the cells of the spermatic line. All cells of the seminiferous epithelium seemed quite normal at the ultrastructural level. However a certain disturbance in the cell localization and some morphological abnormalities involving nuclear structure were seen. Spermatocytes and spermatids normal in appearance were observed, but a great number of cells presented two or more nuclei. Those cells were frequently seen to become degenerated during spermatogenesis. We believe that unbalanced spermatocytes degenerate during the process and only some spermatocytes succeed in fertilizing gametes.